2022
DOI: 10.3389/fnins.2022.790057
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoencephalography Hyperscanning Evidence of Differing Cognitive Strategies Due to Social Role During Auditory Communication

Abstract: Auditory communication is an essential form of human social interaction. However, the intra-brain cortical-oscillatory drivers of auditory communication exchange remain relatively unexplored. We used improvisational music performance to simulate and capture the creativity and turn-taking dynamics of natural auditory communication. Using magnetoencephalography (MEG) hyperscanning in musicians, we targeted brain activity during periods of music communication imagery, and separately analyzed theta (5–7 Hz), alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 95 publications
(115 reference statements)
0
1
0
Order By: Relevance
“…The authors suggest that the identified brain regions might be important for processing auditory information with the encoding of memory. Another study measured MEG from dyads of musicians assuming leader-follower roles while playing MEG-compatible keyboards (Yoneta et al, 2022). They found an increase in occipital alpha and beta power when musicians were assigned the follower role, but not when assigned the leader role.…”
Section: Single-brain Approachmentioning
confidence: 99%
“…The authors suggest that the identified brain regions might be important for processing auditory information with the encoding of memory. Another study measured MEG from dyads of musicians assuming leader-follower roles while playing MEG-compatible keyboards (Yoneta et al, 2022). They found an increase in occipital alpha and beta power when musicians were assigned the follower role, but not when assigned the leader role.…”
Section: Single-brain Approachmentioning
confidence: 99%